Involvement of the Dorsal Vagal Complex in Alcohol-Related Behaviors - Keller, Bailey N.; Hajnal, Andras; Browning, Kirsteen N.; Arnold, Amy C.; Silberman, Yuval (Frontiers in Behavioral Neuroscience, 2022)
The neurobiological mechanisms that regulate the development and maintenance of alcohol use disorder (AUD) are complex and involve a wide variety of within and between systems neuroadaptations. While classic reward, preoccupation, and withdrawal neurocircuits have been heavily studied in terms of AUD, viable treatment targets from this established literature have not proven clinically effective as of yet. Therefore, examination of additional neurocircuitries not classically studied in the context of AUD may provide novel therapeutic targets. Recent studies demonstrate that various neuropeptides systems are important modulators of alcohol reward, seeking, and intake behaviors. This includes neurocircuitry within the dorsal vagal complex (DVC), which is involved in the control of the autonomic nervous system, control of intake of natural rewards like food, and acts as a relay of interoceptive sensory information via interactions of numerous gut-brain peptides and neurotransmitter systems and projections to central and peripheral targets. DVC neuron subtypes produce a variety of neuropeptides and transmitters and project to target brain regions critical for reward such as the mesolimbic dopamine system as well as other limbic areas important for the negative reinforcing and aversive properties of alcohol withdrawal such as the extended amygdala. This suggests the DVC may play a role in the modulation of various aspects of AUD. This review summarizes the current literature on neurotransmitters and neuropeptides systems in the DVC (e.g. norepinephrine, glucagon-like protein 1, neurotensin, cholecystokinin, thyrotropin-releasing hormone), and their relevance to alcohol related behaviors in humans and rodent models for AUD research. A better understanding of the potential role of the DVC in modulating alcohol-related behaviors may lead to the elucidation of novel therapeutic targets for drug development in AUD.